The transportation system and its role in the relations between urban centers and rural areas in the Inaoun Basin Depression - Neddama, Ali; El-Bazoui, Jaouad; Bouberria, Abdelouahed (Journal of Humanities & Social Sciences, 2025)
The transport sector plays a vital role in development at all economic, social and urban levels of each country. The growth and development of each field is closely linked to the extent of this sector’s prosperity and the equipment and infrastructure it requires. Interest in this sector and its development reflects positively on the economic activity of this field and the country in general, in particular. It contributes to the transportation of individuals and works to link production areas with consumption areas.This sector is closely linked to infrastructure and road networks, which can be considered as a vital artery that pumps blood across various parts of the national territory, by facilitating the process of transporting and distributing raw materials and goods to and from areas of production, consumption and investment, and by reducing the differences between regions and regions.For all these considerations, we decided to address the issue of the transportation system and its role in the relations between urban centers and rural areas in the Inawen Basin depression, and we addressed the subject according to its contribution to linking urban centers with the rest of the Kingdom’s territory on the one hand, and through its role in the relations between the countryside and these centers on the other hand, and we concluded its forms and manifestations. These transformations. Which forced us to systematically divide the work into two main points as follows: the road network and its role in the dynamics of the Inawen Basin depression, then the role of the transportation sector in spatial relations.
Keywords: transportation; development; infrastructure; area; road network